Designing the Story Script and the Background for the Animation Spectrum Rise - Agacha, Digi Siera Putra; Sheanny Ocmi Sakti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Indonesia’s low literacy rate serves as the primary inspiration for the design of Spectrum Rise, an animation aimed at fostering reading interest among teenagers through engaging visual media. This final project report discusses the process of scriptwriting and background design in the animation, emphasizing the importance of cohesion between narrative and visual elements. The scriptwriting process employed a structured pipeline combined with improvisational techniques to produce natural dialogue and lively characters. Meanwhile, the background design followed the Multimedia Development Life Cycle (MDLC) approach and utilized digital painting techniques in Clip Studio Paint, supporting both flexibility and efficiency in visual production. The outcome of this design process includes a story script with a strong literacy message and background visuals that enhance mood and character development. The conclusion of this project highlights that integrating technical methods with creative approaches can result in an animation that is not only aesthetically pleasing but also educational. This report is intended to serve as a reference for animators and background designers in developing animation works that convey social messages.